EVALUATION OF THE SCIENTIFIC POTENTIAL OF TEACHERS OF MATHEMATICS ON THE IMPLEMENTATION OF MODERN TEACHING METHODS IN THE PREPARATORY STAGE FROM THE POINT OF VIEW OF THEIR STUDENTS - MOHAMMED, VIYAN HASAN; AHMED AFDEL, RAHMAH (Journal of Duhok University, 2019)
The current research aims at identifying the extent of evaluating the scientific potential of teachers and teachers of mathematics on the implementation of modern teaching methods in the preparatory stage from the point of view of their students. The sample consisted of (120) students with (55) male and (65) female. The researcher used statistical methods as Pearson correlation coefficient, relative weight, t-test for one sample and two independent samples, as well as statistical bag for social sciences (spss). After statistical analysis, The results showed the following:1 - There is a fairly acceptable proportion in general but not the level of ambition in the extent of the scientific potential of teachers and teachers of mathematics to implement modern teaching methods and according to the view of their students.2 - There is a medium percentage of the extent of the scientific potential of teachers and teachers of mathematics on the implementation of modern teaching methods and according to the view of students (males).3 - There is an acceptable percentage in the extent of scientific potential of teachers and teachers of mathematics on the implementation of modern teaching methods and according to the perspective of female students (female).4- There is a statistically significant difference between the male and female students' views on the extent of the scientific potential of teachers and teachers of mathematics on the implementation of modern teaching methods and for male students.The researcher came out with a set of conclusions, recommendations and suggestions. Recommendations for the establishment of advanced training courses by the Directorate of preparation and training to develop the capacity of teachers and teachers of mathematics to implement their scientific lessons in accordance with modern teaching methods